STRUKTUR SOSIAL DALAM PERSPEKTIF SOSIOLOGI HUKUM: KONSEP, FUNGSI, DAN DINAMIKA DALAM MASYARAKAT - Mila Agustin; Nourel Islamay Diandra; Nadya Mahamida; Laila Fatia Maharani; Sinta Bella Farah Kirani; Perina Dwi Astuti; Febra Anjar Kusuma; Rima Yuni Saputri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Social structure is a fundamental concept in the study of sociology of law that explains relatively stable patterns of social relationships within society, including the arrangement of institutions, roles, statuses, and norms that guide human interaction. This article aims to analyze the concept of social structure, its functions within the legal system, and the dynamics that influence social life in a more comprehensive manner. The method used is qualitative research with a literature review approach, drawing on recent and relevant scientific sources to ensure the validity and depth of analysis. The results of the study indicate that social structure plays a crucial role in creating social order, maintaining stability, regulating the distribution of roles and responsibilities, and functioning as an effective mechanism of social control through both formal and informal legal norms, while also shaping how laws are formed, implemented, and enforced within society. In addition, the dynamics of social structure—driven by factors such as social change, modernization, technological advancement, and globalization—significantly influence the evolution and adaptation of legal systems, creating both challenges and opportunities in achieving justice and legal certainty. Therefore, understanding social structure from the perspective of sociology of law is essential for developing a legal system that is responsive to societal changes, ensures fairness, and supports social integration within an increasingly complex society.